Investigation of residential demand response flexibility ıncluding the effects of the covıd-19 pandemic on energy usage habits in turkey - ZEHİR, MUSTAFA ALPARSLAN (My University, 2022)
The COVID-19 pandemic has made a major impact on society and several sectors, including changes in household energy usage. The pandemic brings together changes and negative impacts that should be followed closely for the energy sector. The main purpose of this study is to comprehensively investigate the effects of the COVID-19 pandemic on electrical energy usage habits in Turkey through systematic methods that are adopted in different countries like the US, India, Europe, China, Canada, and Japan. Based on the analysis, residential load management flexibilities are investigated considering the pandemic impacts. The effect of the COVID-19 pandemic on electricity consumption in the energy sector in Turkey is extensively investigated for the first time. The study is of importance also for future pandemics or other conditions such as extreme wind and snow storms that temporarily lead to living and working from home.
Keywords: COVID-19; demand-side management; home energy management; residential energy use; time use survey